2012
DOI: 10.1007/s00210-012-0777-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the uptake of 5-aminolevulinic acid and its methyl ester in keratinocytes and skin

Abstract: Photodynamic therapy is widely used in the treatment of superficial skin cancers. 5-Aminolevulinic acid (ALA) and its methylated form, methyl-ALA (MAL), are frequently used as precursors to photosensitizing substances. Nevertheless, the mechanism of the uptake of ALA and MAL in keratinocytes and of their skin penetration is still controversial. Since both compounds are not sufficiently lipophilic to penetrate through lipid membranes, they must employ specific uptake systems which may vary between different cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
5
11
0
Order By: Relevance
“…This is similar to a prior report with keratinocytes [48]. In the present study, we found that doxycycline could potentiate this effect more prominently with ALA uptake, and to a lesser extent with me-ALA uptake.…”
Section: Discussionsupporting
confidence: 94%
“…This is similar to a prior report with keratinocytes [48]. In the present study, we found that doxycycline could potentiate this effect more prominently with ALA uptake, and to a lesser extent with me-ALA uptake.…”
Section: Discussionsupporting
confidence: 94%
“…The advantage of such a physical stabilization is that unmodified ALA is provided to the cells so uptake and metabolism can start immediately. This faster conversion of ALA into PpIX has been shown in neoplastic keratinocytes [58]. While in healthy keratinocyte cells low level conversion of ALA and MAL to PpIX has been observed, the treatment of neoplastic SCC cells with ALA revealed higher PpIX fluorescence after 2.5 and 4.5 h compared with MAL-treated sample.…”
Section: Enhancing Pdt With Nanoemulsion Technologysupporting
confidence: 60%
“…The drawback of this approach lies in the biological need to have the ester cleaved by cellular enzymes before ALA can enter the heme biosynthetic pathway. Thus, some ALA esters, especially MAL, have been shown to induce less PpIX compared with ALA after the same incubation time [57][58][59]. Additionally, the concentration of short-chained ALA-esters (C1-C3), which is required to induce half-maximal PpIX accumulation, was clearly higher in several cell lines than the corresponding concentration of ALA [56].…”
Section: Enhancing Pdt With Nanoemulsion Technologymentioning
confidence: 99%
“…Cellular localization is an important issue, since it is related with the mechanism of cell death trigger. Photosensitizers localized within mitochondria are mostly associated with the apoptotic (some autophagic) death mechanism involved, i.e., caspase (or caspase-independent) activation and mitochondrial dysfunction (potential disruption of mitochondrial membrane and cytochrome C release) giving rise to morphological changes: bleeding, chromatin condensation and alteration of cell adhesion molecules (29)(30)(31)(32)(33)(34). Confocal images show overlapping of PpIX red fluorescence and MitoTracker Green fluorescence which strongly suggest PpIX mitochondrial localization in infected and non-infected THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%